2022
DOI: 10.21203/rs.3.rs-2352752/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crossover design in triage education: the effectiveness of simulated interactive vs routine training on student nurses' performance in a disaster situation

Abstract: Introduction. One aspect of successful triage is the proper diagnosis of the injured person. For this reason, triage guidelines speed up recognition times and increase services. Therefore, this study aims to develop an interactive triage guideline simulator that can reduce the execution time of the procedure. Method. This study was a crossover design with pre- and posttests for two groups. Each group consisted of 60 students selected using the census method. SIG and teacher training sessions were conducted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Knowledge There were 9 programs evaluating knowledge (64%, 9 out of 14), 2 of the 9 programs said there was no significant difference before and after the intervention (1.84 ± 1 vs 2.09 ± 0.93), the other five programs showed a difference between scores before and after the intervention was given (Hu et al, (2021) There are 7 programs that evaluate related skills (50%, 7 out of 14), these seven programs are given by different methods, namely by education, lectures and training. The results showed an increase between pre-test and post-test scores, but there was no significant difference between the intervention group and the control group (Xia et al, (2019); Huh & Kang, (2018); Cicero et al, (2018); Heidarzadeh et al, (2020); Hosseini et al, (2023); Aghababaeian et al, (2013); Pouraghaei et al, (2017)). c. Attitude There were 3 programs that evaluated attitudes (21%, 3 out of 14), showing no significant difference in attitudes between the experimental group and the control group (3.00 ± 1.19 vs 2.81 ± 1.01).…”
Section: Results Of the Evaluation Of Disaster Triage Education And T...mentioning
confidence: 89%
See 2 more Smart Citations
“…Knowledge There were 9 programs evaluating knowledge (64%, 9 out of 14), 2 of the 9 programs said there was no significant difference before and after the intervention (1.84 ± 1 vs 2.09 ± 0.93), the other five programs showed a difference between scores before and after the intervention was given (Hu et al, (2021) There are 7 programs that evaluate related skills (50%, 7 out of 14), these seven programs are given by different methods, namely by education, lectures and training. The results showed an increase between pre-test and post-test scores, but there was no significant difference between the intervention group and the control group (Xia et al, (2019); Huh & Kang, (2018); Cicero et al, (2018); Heidarzadeh et al, (2020); Hosseini et al, (2023); Aghababaeian et al, (2013); Pouraghaei et al, (2017)). c. Attitude There were 3 programs that evaluated attitudes (21%, 3 out of 14), showing no significant difference in attitudes between the experimental group and the control group (3.00 ± 1.19 vs 2.81 ± 1.01).…”
Section: Results Of the Evaluation Of Disaster Triage Education And T...mentioning
confidence: 89%
“…Participants were given a debriefing for 1 hour before the simulation and given a short presentation to describe the scenario for 5 minutes. The debriefing focused on how to combine clinical reasoning and triage principles in clinical decision-making with the integration of clinical reasoning model principles (Alshamari et al, (2023); Cicero et al, (2018); Hosseini et al, (2023); Hu et al, (2021a); Lee et al, (2016)). However, this study has limitations as it only uses five databases, so there may be relevant articles in other databases…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that education remains relevant and effective in the 21st century, it is crucial for universities to adapt and embrace the potential offered by evolving technologies (3). This entails integrating digital platforms, such as interactive games (4)(5)(6), virtual simulators (7), wearable tech devices (8), or social media channels, into classroom teaching.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of educational programs that interact with students will be strongly felt in the future due to the shift in learning generations (13). Several studies have examined the relationship between educational games and intrinsic motivation (5,6,14,15). Park reported that learners who actively engaged with these games exhibited higher levels of intrinsic motivation (16).…”
Section: Introductionmentioning
confidence: 99%